PEMBAKUAN SERAPAN BAHASA ARAB DALAM BAHASA INDONESIA PADA FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA (DSN-MUI) - Permatasari, R. Indah; Berhimin, Ahmad (An Nuqud Journal of Islamic Economics, 2022)
There are many words or terms of Islamic Economic in the instructions compilation of National Sharia Board – Indonesia Council of Ulama in Arabic. The instruction of National Sharia Board – Indonesia Council of Ulama is a law product that is published as the first step of National Sharia Board – Indonesia Council of Ulama in socializing the instructions of National Sharia Board and the Islamic Economic in general. The goals of the research are (1) analizing the absorption standard from Arabic language into Indonesian in the instructions of National Sharia Board (2) Analizing the terms absorbed from Arabic language into Indonesian in the instructions of National Sharia Board that are standarded in The Great Dictionary of the Indonesian Language. This research uses Match Method as the data analysing technique. Match method is a way to analyze data in answering the problem researched with determining tool comes from outside the language. The result of the research shows that the absorption standard from Arabic language into Indonesian in the instructions of National Sharia Board – Indonesia Council of Ulama through the following steps, 1) selection, 2) codification, 3) function description, 4) agreement. The research found that there are 20 Islamic Economic terms in Indonesian which are absorbed from Arabic language in the instructions of National Sharia Board – Indonesia Council of Ulama about the contract standarded in The Great Dictionary of the Indonesian Language, the fifth edition. Those are Akad, Istisna’, Salam, Wadi’ah, Wakalah, Musyarakah, Ijarah, Mudharabah, Murabahah, Hibah, Shahibul maal, Mudharib, Muwwakil, Kafil, Sukuk, syarik, Wa’d, Riba, Ikhtikar, Gharar.